Daya Tarik Minat Generasi Z Dalam Bertransaksi Menggunakan Financial Technology (E-Wallet): (Studi Kasus Pelanggan E-Commerce Di DKI Jakarta) - Alifiyah Nabilah Rahman; Setiyo Purwanto (CV. Strata Persada Academia, 2023)
To maximize the use of technology in expediting financial services, financial technology makes transactions in the financial industry easier, more practical, and efficient. Non-cash payment methods, including e-wallets, are highly sought after by consumers. The development of financial technology is common among Indonesians, especially generation Z. Therefore, the population determined in this research case study is the people of DKI Jakarta province who belong to generation Z. The sampling technique in this study was purposive sampling method. The data used used primary data, namely by distributing questionnaires which were responded to by 100 respondents. The analysis technique used in this study using multiple linear regression tests using the SPSS 25 program. The results showed that the variables of effectiveness, trust, and perceived convenience had the same t significance value of 0.000 where the t value was smaller than 0.05. This shows that effectiveness, trust, and perceived ease of use affect the interest in transactions using financial technology (e-wallet) together by 80.4% and the remaining 19.6% is influenced by other factors.